# 3x+11=8 solving equations with more than one operation

by Po Po
(Texas)

if you have 3x + 11 = 8 how do you solve it?

How do you rearrange the parts of the equation so that “x” IS ON ONE SIDE OF THE EQUAL SIGN BY ITSELF, and there are no “x’s” on the other side of the equation.

### Comments for 3x+11=8 solving equations with more than one operation

 May 14, 2012 3x+11=8 by: Staff Question: by Po Po (Texas) if you have 3x+11=8 how do you solve it? Answer: Think about your goal. Solving an equation for x means you must rearrange the parts of the equation so that “x” IS ON ONE SIDE OF THE EQUAL SIGN BY ITSELF, and there are no “x’s” on the other side of the equation. x = ….. is the solution How do you do it? You solve equations using INVERSE operations. You must also use Inverse Operations in reverse PEMDAS order. An Inverse Operation reverses the effect of an operation. The inverse operation of addition is subtraction. The inverse operation of subtraction is addition. The inverse operation of multiplication is division. The inverse operation of division is multiplication. The problem you submitted is: 3x + 11 = 8 To solve the problem for x, you must eliminate the 11 and the 3 from the left side of the equation. Once these two numbers are eliminated, “x” will be on the left hand side of the equal sign by itself. At that point you are finished. Eliminating the +11 from the left side of the equation: Since the operation of +11 is addition, the “inverse operation” is subtraction (-11). To eliminate the +11 from the left hand side of the equation, subtract 11 from both sides of the equation. 3x + 11 - 11 = 8 - 11 3x + 0 = 8 - 11 3x = 8 - 11 3x = -3 3*x = -3 Eliminating the 3* from the left side of the equation: Since the operation 3* is multiplication, the “inverse operation” is division (÷ 3). To eliminate the 3* from the left hand side of the equation, divide both sides of the equation by 3. 3x / 3 = -3 / 3 x * (3 / 3) = -3 / 3 x * (1) = -3 / 3 x = -3 / 3 x = -1 >>> the final answer is: x = -1 Check the solution by substituting -1 for x in the original equation 3x = 8 – 11 3 * (-1) = 8 - 11 -3 = 8 - 11 -3 = -3, OK → x = -1 is a valid solution Thanks for writing. Staff www.solving-math-problems.com